2016
DOI: 10.1038/srep19358
|View full text |Cite
|
Sign up to set email alerts
|

Localized crystallization in shear bands of a metallic glass

Abstract: Stress-induced viscous flow is the characteristic of atomic movements during plastic deformation of metallic glasses in the absence of substantial temperature increase, which suggests that stress state plays an important role in mechanically induced crystallization in a metallic glass. However, it is poorly understood. Here, we report on the stress-induced localized crystallization in individual shear bands of Zr60Al15Ni25 metallic glass subjected to cold rolling. We find that crystallization in individual she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 37 publications
(39 reference statements)
0
19
0
Order By: Relevance
“…The improvement of the mechanical properties in BMG is also reported by creating second phase inside the amorphous matrix 17,18 . Yan et al (2015) reported about the stress-induced nano-crystallization at the shear plane due to the localized heating in Zr 60 Al 15 Ni 25 BMG 19 . Metastable B2 reinforced BMG composite of Zr 48 Cu 47.5 Al 4 Nb 0.5 alloy was reported with strong strain-hardening capability and large elastic strain limit by Wu et al 20 .…”
Section: Activation Energy (E a ) And Avrami Exponential Factor (N) Hmentioning
confidence: 99%
“…The improvement of the mechanical properties in BMG is also reported by creating second phase inside the amorphous matrix 17,18 . Yan et al (2015) reported about the stress-induced nano-crystallization at the shear plane due to the localized heating in Zr 60 Al 15 Ni 25 BMG 19 . Metastable B2 reinforced BMG composite of Zr 48 Cu 47.5 Al 4 Nb 0.5 alloy was reported with strong strain-hardening capability and large elastic strain limit by Wu et al 20 .…”
Section: Activation Energy (E a ) And Avrami Exponential Factor (N) Hmentioning
confidence: 99%
“…During the past years, numerous studies have been carried out in order to understand the SB nucleation, and relate them to the defects given in crystalline metals 44 45 46 47 . Especially, it would be desirable to have studies directly correlating the evolution of the SB and matrix structure to the applied strain, allowing us to easily connect the atomic structure evolution to the stress-strain curve.…”
Section: Resultsmentioning
confidence: 99%
“…The deformation of amorphous alloys at low temperatures (significantly below the glass transition temperature) is localized and is carried out by the formation and propagation of shear bands. A lot of works [5,11,12,14,23,24,[28][29][30][31] are devoted to the study of the processes of shear band formation and crystallization under deformation. Nanocrystal formation in shear bands and their vicinity is caused by an enhanced value of the diffusion coefficient in these regions.…”
Section: Crystallization Of the Alloy During Deformationmentioning
confidence: 99%
“…The reasons for diffusion acceleration are usually related to either a local significant but short-term (~30 ps) temperature rise in the region of deformation localization [32,33] or a decrease in the material density (an increase in the free volume fraction) in a shear band [34,35]. In a number of works, for example, in [30], it is shown that not only shear bands but also compressed and extended regions are formed under deformation. The authors of [30] explained the formation of these regions in the following way.…”
Section: Crystallization Of the Alloy During Deformationmentioning
confidence: 99%